Women, crime and character in the 20th century - Lacey, Nicola (Journal of the British Academy, 2018)
This paper investigates the fate of women in the 20th-century English criminal justice system. Drawing on both literary and legal sources, I venture an explanation for the relatively low rates at which women are adjudged to have committed crimes, despite the huge social changes in their legal, political and economic position during the course of the last hundred years. First, I present some statistics to illustrate trends in female criminalisation and incarceration during the 20th century. Second, I sketch and compare the conceptions of selfhood and responsible agency to be found in criminology, criminal law, the criminal process and 20th-century literary fiction. Third, I focus on literary representations of women, exploring what light women’s counter-normative behaviour in fiction can shed on the patterns of female criminalisation. And finally, I draw out the implications of this interpretation for methodology in the social sciences